Modelo Arquitectónico para Interoperabilidad entre Instituciones Prestadoras de Salud en Colombia. - Castrillón, Helder Y.; González, Carolina; López, Diego M. (Biomedical Engineering Journal / Revista Ingeniería Biomédica)
Nowadays governments, health services organizations and software developers face the need to improve the efficiency of information systems in health through information management and ICT implementation. One of the areas of interest is the development of interoperability profiles that allow exchange information and improve collaboration between different actors in the health system. The aim of this paper is to define and validate an architectural model of interoperability between information systems on IPS in Colombia. The model, grounded in Colombian legislation, suggests the use of SOA as a reference to define the software architecture and HL7 standard for the exchange of messages and clinical documents. Subsequently the model is evaluated by a group of professionals with experience in information systems development and piloted based on two interoperability scenarios in three IPS of Popayán. The model aims to provide a methodology for software modeling and development among health services organizations, improving the level of understanding and control over information transactions present in the delivery of services.